The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1103/physrevlett.93.244802
|View full text |Cite
|
Sign up to set email alerts
|

Beam-Size Measurement with Optical Diffraction Radiation at KEK Accelerator Test Facility

Abstract: An experiment on the investigation of optical diffraction radiation (ODR) from a slit target as a possible tool for noninvasive electron beam-size diagnostics has been performed at the KEK accelerator test facility. The experimental setup has been installed at the diagnostics section of the extraction line. We have performed the first incoherent ODR observation from a slit target. The measured angular distributions are in reasonable agreement with the theoretical expectation. The beam-size effect onto the ODR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 4 publications
2
79
0
Order By: Relevance
“…These effects are often partially obscured by beam-offset and beam-divergence contributions. More recently, an unusually low-divergence beam ( 1:5 rad) allowed ODR far-field data from a slit aperture to be analyzed for beam-size effects [13]. These data were obtained via a scanning-mirror plus detector geometry, but the scan took ten minutes.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are often partially obscured by beam-offset and beam-divergence contributions. More recently, an unusually low-divergence beam ( 1:5 rad) allowed ODR far-field data from a slit aperture to be analyzed for beam-size effects [13]. These data were obtained via a scanning-mirror plus detector geometry, but the scan took ten minutes.…”
Section: Introductionmentioning
confidence: 99%
“…10). The knife edge was fabricated from a 300 m thick single crystal of silicon using etch and mask and then coated with gold [2].…”
Section: Interaction Chambermentioning
confidence: 99%
“…The normal techniques of beam size measurement, for example, wire scanners and screens which intersect the charged particle beam, are not applicable when the bunch charge density is sufficiently large to damage the material placed in the beam. In these scenarios noninvasive techniques must be used such as optical diffraction radiation [2] or methods based on laser interactions with electron beams. A review of beam size measurement of electron beams can be found in [3].…”
Section: Introductionmentioning
confidence: 99%
“…The first application of this technique to the particle beam diagnostics has been performed at ATF (KEK) ( [3], [4], [5]). …”
Section: Introductionmentioning
confidence: 99%